(untitled) (MAUSAM, 2022)
Quantifying energy balance components over cropped area helps in better understanding of the water balance and helps in economic use of water. A field experiment was conducted during summer 2021 at Tamil Nadu Agricultural University, Coimbatore to study the change of energy balance partitioning and evapotranspiration rate at each growth stage of sorghum based intercropping system. The energy balance components and evapotranspiration rate of crops was estimated by Bowen Ratio Energy Balance (BREB) method. The results revealed that the energy balance partitioning varied among crop growth stages. The variation in LE/Rn was 0.61(seedling) to 0.86(flowering).This variation was based on amount of net radiation, foliage cover, soil moisture condition, vapour pressure deficit .The total evapotranspiration for the crop period was observed to be 322 mm. The ET requirement was the highest during vegetative stage when the total LE was found to be maximum.